2022
DOI: 10.1108/jhti-09-2021-0237
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus: choking global and Indian tourism economy and leaving industry on the ventilator

Abstract: PurposeThis study examines the economic crisis caused by coronavirus on the global tourism industry in general and the Indian tourism industry in particular. This paper highlights the strategies that tourism companies should implement in times of crisis to reduce the negative impact. It also discovers the business opportunities which can be offered amid this deadly pandemic.Design/methodology/approachThe study is based on a systematic literature review. The literature has been explored by utilizing the keyword… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Besides impacting global health, the COVID-19 pandemic possessed numerous adverse consequences on the economic, social, mental/psychological, environmental, cultural, and political aspects . The growth of the enzyme market depends on the demand for the enzymes’ end-uses, e.g., cleaning, biofuel, food/beverage, pharmacy, animal feed, etc. , Even though the industrial enzyme market witnessed a significant evolution in terms of its revenue during the past decade, it was dramatically affected adversely in 2020 due to the coronavirus pandemic. It was reported that, during the 2020 pandemic year, the highest enzyme market share was that of the food and beverage sectors, as well as the house care products and cleansers .…”
Section: Effect Of Coronaviruses On Global Enzyme Productionmentioning
confidence: 99%
See 4 more Smart Citations
“…Besides impacting global health, the COVID-19 pandemic possessed numerous adverse consequences on the economic, social, mental/psychological, environmental, cultural, and political aspects . The growth of the enzyme market depends on the demand for the enzymes’ end-uses, e.g., cleaning, biofuel, food/beverage, pharmacy, animal feed, etc. , Even though the industrial enzyme market witnessed a significant evolution in terms of its revenue during the past decade, it was dramatically affected adversely in 2020 due to the coronavirus pandemic. It was reported that, during the 2020 pandemic year, the highest enzyme market share was that of the food and beverage sectors, as well as the house care products and cleansers .…”
Section: Effect Of Coronaviruses On Global Enzyme Productionmentioning
confidence: 99%
“…It was reported that, during the 2020 pandemic year, the highest enzyme market share was that of the food and beverage sectors, as well as the house care products and cleansers . The demand for enzymes for industrial applications dropped severely during the last two years because of disruptions in global supply chains . However, most of the pioneering companies in their fields tried to return their production intensity back and strengthen their production in other relevant products (e.g., sanitizers and handwashes).…”
Section: Effect Of Coronaviruses On Global Enzyme Productionmentioning
confidence: 99%
See 3 more Smart Citations